A framework for the assessment of multi-skilling in work units. - Sevastos, Peter P. (Curtin University, 1986)
Multi-skilling, an organisational strategy aimed at increasing the skill repertoire of the worker with the intent of facilitating the role and task flexibility among organisational members, is investigated.A literature review on the subject identified a number of factors contributing towards the development of a multi-skilled workforce. These ranged from the abolition of demarcation restrictions between jobs and skill-based pay systems, to the modification of the supervisory role. However, the literature fails to consider the role of technology in such developments. It was suggested that this was central to the development of skills.A framework was proposed that hypothesized a relationship between technological uncertainty the extent to which task activities are varied and difficult and skill requirements. It was further hypothesized that technology influences the structuring of activities within organisational subsystems. It was suggested that these would act either to facilitate or inhibit multi-skilling development.The structuring of activities within a unit consist of specialisation (the number of different tasks assigned to the unit); standardisation (the degree to which policies, rules, and procedures are formalised and used to guide action); interchangeability (the extent to which A can perform Bs job at short notice, and vice versa); locus of authority (the source of decision-making authority within the unit, for example, the supervisor rather than the worker); and skill heterogeneity (the variability in skill composition among unit members).A preliminary evaluation of the framework was carried out in an organisation engaged in the processing of mineral ore, with a largely semi-skilled workforce (N=165), where a multi-skilling programme was in progress.Evidence was presented that suggested a relationship between the level of technological uncertainty and skill development. However, the results failed to confirm the pervasive influence of technology with regard to the structuring of activities within subsystems. Instead, technological uncertainty was significantly related to the design of jobs, and specifically to the degree of the standardisation of jobs of organisational members. Also, contrary to the anticipated direction, there was an association between perceived standardisation of activities within subsystems and job satisfaction.